Associations among incontinence, incontinence‐associated dermatitis and pressure injuries in older nursing home residents. Issue 3 (16th May 2022) - Hoedl, Manuela; Eglseer, Doris
Abstract: Objective: This study was conducted to investigate the association between incontinence (INC), incontinence‐associated dermatitis (IAD) and (nosocomial) pressure injuries (PI) in nursing home residents aged 60 years or older. Methods: We included 3725 older residents in this cross‐sectional, multisite secondary data analysis. A standardized questionnaire was used that included demographic data and other data including care dependency, as well as data on INC, IAD and PI. We analysed the data using methods of descriptive statistics, bivariate analysis and univariable/multivariate regressions. Results: Our results showed that risks for malnutrition, diseases of the skin and subcutaneous tissue, and having a catheter for INC reasons were associated with a higher risk for (nosocomial) PI in this population. Independent of their age group, specifically residents with a catheter had a higher risk of developing a (nosocomial) PI. Conclusions: We strongly recommend carrying out further studies to examine the association between the risk of malnutrition and PI. To address other aspects of nutritional status, studies on associations between obesity on INC, IAD as well as PI would also be of great interest.